PENERAPAN ASAS TRANSITOIR ATAU ASAS LEX FAVOR REO PADA PELAKU TINDAK PIDANA YANG DIVONIS PIDANA MATI SAAT PERALIHAN KUHP - Mochamad Febrian Nurdin (Sabtida, 2024)
ABSTRACT At the beginning of 2023, Indonesia officially passed its new Criminal Code, namely Law No. 01 of 2023 concerning the Criminal Code. Although this New Criminal Code has been passed in January 2023, this New Criminal Code does not immediately take effect, but is valid from 3 years after its promulgation, so that everyone knows about it (Article 624 of the New Criminal Code). At the time the new penal code was passed, it was a coincidence that Indonesia was in the midst of a major case involving a former police general who was sentenced to death in a court of first instance. So that raises questions among the public about whether the New Criminal Code can be an obstacle to the execution of death row criminals. Because of this, the author takes the formulation of the problem: 1) What is the difference from the Transitoir Principle or the Lex Favor Reo Principle in the Old Criminal Code and the New Criminal Code? 2) What is the juridical analysis of criminal offenders sentenced to death during the transition process from the old Criminal Code to the new Criminal Code? This research uses normative juridical, with a statutory approach. Keywords: Transitoir Principle, Lex Favor Reo Principle, Death Penalty, New Criminal Code. ABSTRAK Pada awal bulan 2023 kemarin, Indonesia secara resmi mengsahkan KUHP nya yang baru yakni UU No. 01 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana. Meskipun KUHP Baru ini telah disahkan pada Januari 2023, akan tetapi KUHP Baru ini tidak serta merta langsung berlaku, akan tetapi berlaku terhitung sejak 3 tahun setelah diundangkannya, agar setiap orang mengetahuinya (Pasal 624 KUHP Baru). Pada saat KUHP Baru ini disahkan, merupakan suatu kebetulan di Indonesia sedang dilanda kasus besar yang melibatkan mantan jendral polisi yang divonis pidana mati pada pengadilan tingkat pertama. Sehingga hal tersebut menimbulkan pertanyaan dikalangan masyarakat tentang apakah KUHP Baru bisa menjadi penghalang bagi eksekusi pidana mati pelaku tindak pidana. Karena hal tersebut maka penulis mengambil rumusan masalah: 1) Apa Perbedaan Dari Asas Transitoir atau Asas Lex Favor Reo Yang Ada Pada KUHP Lama dan KUHP Baru? 2) Bagaimana Analisis Yuridis Terhadap Pelaku Tindak Pidana Yang Divonis Pidana Mati Pada Saat Proses Peralihan dari KUHP Lama ke KUHP Baru? Penelitian ini menggunakan yuridis normatif, dengan pendekatan perundang-undangan. Kata kunci: Asas Transitoir, Asas Lex Favor Reo, Pidana Mati, KUHP Baru.